Iatrogenic soft palate cleft during difficult intubation – a case report: Lesão iatrogénica do palato durante abordagem da via aérea – caso clínico - Denise de Noronha (Journal of the Portuguese Society of Anesthesiology, 2023)
Endotracheal intubation is an essential skill. Videolaryngoscopy has gained popularity as an alternative intubation device,becoming a rescue tool in difficult airway intubation protocols and often considered as the first approach during COVID-19 pandemic due the increased first attempt intubation success rates. However, the loss of depth perception and the shift of the focus from the patient to the video monitor can lead to an orofaringeal blind introduction of the endotracheal tube resulting in minor to severe injuries. We report a case of a patient with a severe tonsilar pillar cleft that passed unnoticed, that required palatoplasty and tracheostomy.